Personalized Neural Networks Underlie Individual Differences in Ethnic Identity Exploration and Resolution. (16th April 2022) - Constante, Kevin; Demidenko, Michael I.; Huntley, Edward D.; Rivas‐Drake, Deborah; Keating, Daniel P.; Beltz, Adriene M.
Abstract : This study examined how ethnic identity relates to large‐scale brain networks implicated in social interactions, social cognition, self‐definition, and cognitive control. Group Iterative Multiple Model Estimation (GIMME) was used to create sparse, person‐specific networks among the default mode and frontoparietal resting‐state networks in a diverse sample of 104 youths aged 17–21. Links between neural density (i.e., number of connections within and between these networks) and ethnic identity exploration and resolution were evaluated in the full sample. Ethnic identity resolution was positively related to frontoparietal network density, suggesting that having clarity about one's ethnic group membership is associated with brain network organization reflecting cognitive control. These findings help fill a critical knowledge gap about the neural underpinnings of ethnic identity.